Populasi dan Karakteristik Pohon Sarang Kakatua Jambul Kuning (Cacatua sulphurea) di Kawasan TWA Studi Kasus Kawasan Rimba Kenari Desa Kamot Kecamatan Alor Timur Laut Kabupaten Alor - Yosua Prastowo Pehi; Maria M. E. Purnama; Fadlan Pramatana; Norman P. L. B. Riwu Kaho (Wana Lestari, 2025)
The Yellow-crested Cockatoo (Cacatua sulphurea), a critically endangered subspecies of the Yellow-crested Cockatoo, faces population pressure due to illegal hunting and habitat destruction. This study aimed to analyze the population and characteristics of Yellow-crested Cockatoo nest trees in the Tuti Adagae Natural Reserve (TWA), a case study area of the canary forest in Kamot Village, North East Alor District, Alor Regency. The research method involved field surveys, direct observation, and measurements of the characteristics of the nest trees used by the cockatoos. The population survey was conducted by recording the number of individuals observed along the observation route, while nest trees were identified and their characteristics, including tree species, diameter, and height of the nest The study concluded that although the Tuti Adagae National Park (TWA) provides habitat for the Yellow-crested Cockatoo, the species' population remains vulnerable. Habitat destruction and microclimate factors pose serious challenges. Conservation recommendations include protecting existing nesting trees, restoring habitat through appropriate tree planting, and conducting regular population monitoring to support the survival of this endangered species. hole, were measured. Analysis of nest tree characteristics revealed that cockatoos tend to select tall, large-diameter trees with natural holes. In the Tuti Adagae TWA, a case study of the canary forest area of Kamot Village, North East Alor District, Alor Regency, for example, the identified nest trees have an average height of 15 to 19 meters, with nest holes at an average height of 15 to 20 meters from the ground surface. Study concluded that although the Tuti Adagae National Park (TWA) provides habitat for the Yellow-crested Cockatoo, the species' population remains vulnerable. Habitat destruction and microclimate factors pose serious challenges. Conservation recommendations include protecting existing nesting trees, restoring habitat through appropriate tree planting, and conducting regular population monitoring to support the survival of this endangered species.